2014
DOI: 10.3945/ajcn.114.087452
|View full text |Cite
|
Sign up to set email alerts
|

Impact of energy density on liking for sweet beverages and caloric-adjustment conditioning in children

Abstract: Background: The contribution of sweet beverages to weight gain in children is controversial; the impact of these beverages on caloric adjustment needs clarification. Objective: We studied the influence of energy-density (ED) conditioning on the liking for sweet beverages and caloric adjustment after their consumption in children. Design: We used a within-subject design. Forty-four 8-11-y-old children were exposed to the following 2 distinctly flavored, sweetened beverages: a high-energy (HE) version (150 kcal)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…We previously showed that caloric compensation ability was improved after repeated exposure to a preload. 35 This study documented for the first time the level of COMPX at a meal after an energy-dense preload in preschool French children. This level was similar to COMPX measured in previous Scottish and American studies.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that caloric compensation ability was improved after repeated exposure to a preload. 35 This study documented for the first time the level of COMPX at a meal after an energy-dense preload in preschool French children. This level was similar to COMPX measured in previous Scottish and American studies.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of hunger on food choices leads to considering the importance of energy density in driving children food preferences and energy intake control. It was indeed shown, in sweet-flavored beverages which were caloric or not (based on use of sucrose or sucralose, a nonnutritive sweetener), that energy density seems to condition more stable flavor preferences than sweetness alone (Remy et al 2014). Furthermore, this study shows that energy density is not detected on the short term after consumption (i.e., within 1 hour post consumption of a new beverage) but is learned through repeated exposures.…”
Section: School Age: a Curious Autonomous Eater Still Framed By Parementioning
confidence: 58%
“…In contrast, attempts to extend this model to humans have produced several positive findings but also several null results, and effects are sometimes weak or unreliable. While some studies have shown clear evidence of de novo learning produced under controlled conditions (e.g., [45][46][47][48][49][50][51][52]) several others report null results (e.g., [53][54][55][56][57]). Sometimes results are seen in only some participants (e.g., unrestrained eaters [58]) or in some dependent measures (e.g., liking, intake, choice) but not others.…”
Section: Discussionmentioning
confidence: 99%